The “secrets” of English private tutoring in China: Chinese students’ experiences of study abroad test preparation in cram schools - Zhang, Cong; Zhang, Yi; Gao, Yun (Frontiers in Psychology, 2023)
English private tutoring, also known as “shadow education” has been an important way that international students rely on for overseas test preparation. Despite the plethora of research on private tutoring in various countries and regions, scarce research focuses on the type of EPT that prepares students for overseas tests. Therefore, this study investigated the experience and perceptions of EPT in preparing for overseas writing tests of 187 Chinese students through retrospective interviews and questionnaires. The present study investigated Chinese students’ experience in and perceptions of EPT for study abroad writing test preparation. The results showed that most students received EPT in writing in various ways at cram schools and they devoted themselves to EPT in cram schools intensively. They favored EPT in cram schools mainly because the test-taking strategies taught there could help them obtain a higher grade on the writing section in overseas tests. With respect to writing teaching in cram schools, the most frequent teaching activities included teaching test-taking strategies and providing writing templates. Although most students acknowledged the usefulness of EPT in writing in terms of preparing themselves for the writing test, it was not necessarily the case for improving their general writing abilities. The students believed that the writing instruction was test-oriented and had a ceiling effect in improving their general writing abilities. However, with enough long time in EPT, the cramming nature of cram schools can be less obvious.